2020
DOI: 10.1093/humrep/dez284
|View full text |Cite|
|
Sign up to set email alerts
|

Septum resection in women with a septate uterus: a cohort study

Abstract: Study question Does septum resection improve reproductive outcomes in women with a septate uterus? Summary answer In women with a septate uterus, septum resection does not increase live birth rate nor does it decrease the rates of pregnancy loss or preterm birth, compared with expectant management. What is known already The septate uterus is the most common u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 24 publications
0
44
0
4
Order By: Relevance
“…The ESHRE/ESGE definition included as septate many uteri with a very small internal indentation depth, which would be considered benign by other leading groups of experts and according to the current ASRM criteria. Furthermore, a recent multicenter study showed that women with septate uterus, loosely defined according to ESHRE/ESGE, who underwent metroplasty did not have any increased benefit from the intervention in comparison to those who were managed expectantly.…”
Section: Discussionmentioning
confidence: 99%
“…The ESHRE/ESGE definition included as septate many uteri with a very small internal indentation depth, which would be considered benign by other leading groups of experts and according to the current ASRM criteria. Furthermore, a recent multicenter study showed that women with septate uterus, loosely defined according to ESHRE/ESGE, who underwent metroplasty did not have any increased benefit from the intervention in comparison to those who were managed expectantly.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding women with a septate uterus, an international multicenter cohort study on 257 women has recently been published. 50 In this study, live birth occurred in 80 of 151 women following a septum resection (53%) compared with 76 of 106 women following expectant management (71.7%; hazard ratio [HR]: 0.71, 95%: CI 0.49-1.02) and ongoing pregnancy occurred in 89 women who underwent septum resection (58.9%) compared with 80 women who had expectant management (75.5%; HR: 0.74, 95% CI: 0.52-1.06). Despite correcting for the most relevant patient characteristics, the results might not be free of residual confounding and need to be confirmed in RCTs.…”
Section: Expectant Managementmentioning
confidence: 99%
“…However, a systematic review, a large cohort study, and the TRUST trial showed no benefits from hysteroscopic septum resection in infertile women in comparison to expectant management. [63][64][65] But it is possible that women treated expectantly underwent diagnostic procedures with tubal flushing for diagnosing the septum (i.e., HSG, sonohysterography, hysteroscopy). These diagnostic procedures can mask the effect of tubal flushing associated with metroplasty, when the group without surgical intervention underwent tubal flushing according to study protocols, which are focused directly on surgical procedure, but not on the associated tubal flushing.…”
Section: Diagnostic Hysteroscopy and Operative Hysteroscopymentioning
confidence: 99%